Effects of different supplementary feeds on the growth performance and survival of Labeo bata fry (Jahangirnagar University Journal of Biological Sciences, 2018)
An experiment was conducted with Labeo bata fry for 60 days to examine the growth performance and survival in response to three supplementary feeds i.e. wheat bran, maize bran and mixed diet. The length gain, percent length gain, weight gain, percent weight gain and specific growth of the fry were found significantly higher (p